1994
DOI: 10.1002/bjs.1800810421
|View full text |Cite
|
Sign up to set email alerts
|

Value of Nissen fundoplication in patients with gastro-oesophageal reflux judged by long-term symptom control

Abstract: A total of 160 patients treated by Nissen fundoplication for uncomplicated gastro-oesophageal reflux disease were studied over a 20-year period. Recurrent reflux and side-effects were assessed yearly after surgery. No objective tests for reflux were performed during follow-up if patients were asymptomatic. Perioperative mortality and technique-related morbidity rates were both 2 per cent. At the latest evaluation, 79 per cent of patients were completely relieved of reflux symptoms, 85 per cent had symptoms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…The reported success rates vary from 76% in one 20-year follow-up study to 91% in an extrapolated actuarial analysis [9][10][11][12]. Spechler et al [2] reported a 62% use of antireflux medications 10 years after surgical fundoplication in a randomized controlled trial comparing open fundoplication and medical treatment (anti-H 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reported success rates vary from 76% in one 20-year follow-up study to 91% in an extrapolated actuarial analysis [9][10][11][12]. Spechler et al [2] reported a 62% use of antireflux medications 10 years after surgical fundoplication in a randomized controlled trial comparing open fundoplication and medical treatment (anti-H 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgery for GERD has been shown to be effective over long-term follow-up and was reserved for patients with complications of GERD or those who did not respond to maximum medical therapy [9]. In a prospective randomized controlled trial comparing surgical and medical therapy of GERD, Lundell et al [13] found open fundoplication to be superior to maintenance omeprazole (AstraZeneca PLC, Sweden) therapy in GERD patients.…”
mentioning
confidence: 99%
“…Many centers that have offered this procedure over the past 10 years have reported an increase in referral of patients controlled on maintenance PPI therapy who choose to have the laparoscopic surgical option in preference to longterm medication. The result of surgery in this group of patients has been shown to be excellent [3,5,9].…”
mentioning
confidence: 99%
“…Several reports have shown laparoscopic Nissen fundoplication to be an established treatment option for chronic GERD [8,[12][13][14][15]. The use of antireflux surgery in patients with persistent symptoms despite therapy with PPIs has been discouraged because of the evidence that positive response to medical therapy is predictive of surgical success [9,16,17].…”
Section: Discussionmentioning
confidence: 99%